The Establishment of International University Campuses as a Key Factor in the Development of Local Tourism in the Turkestan Region in Kazakhstan: Economic and Legal Aspects - ALTYNBASSOV, Bakhyt; MYRZATAYEV, Nurmukhamed; BARLYKOV, Yerbolat; KOZHABEKOV, Sovet; NAZIKOVA, Zhanagul; NARENOVA, Aiman; BAYANBAYEVA, Aigerim (Journal of Environmental Management and Tourism, 2021)
This article discusses legal and economic issues in the higher education and tourism industry in the context of Kazakhstan. The study revealed that the creation of international university campuses in the Turkestan region can enable to develop a local tourism and become an attractive tourist destination and international educational hub in Central Asia. It is suggested to establish these campuses in partnership with the world's leading universities based on the experience of Nazarbayev University. There is a great chance to attract international students and tourists as well as establish Kazakhstan's Silicon Valley. To create endowment funds and ensure the financial independence of universities, it is proposed to pass a special land granting law enabling regions to allocate land plots to universities on a gratuitous basis, as seen in practice in the USA. Additionally, it was concluded that this region in geographical, territorial, climatic terms as well as the historical role of Turkestan are very favourable for the development of international tourism. The research was conducted based on the documentary analysis method and secondary data analysis. Legal acts and state programs and acts launched by the government in higher education, tourism, and hospitality industries were collected from the official websites of state bodies and analyzed.